Responses of Surface Runoff to Climate Change and Human Activities in the Arid Region of Central Asia: A Case Study in the Tarim River Basin, China - Xu, Changchun; Chen, Yaning; Chen, Yapeng; Zhao, Ruifeng; Ding, Hui (Environmental management (New York), 2013)
Based on hydrological and climatic data and land use/cover change data covering the period from 1957 to 2009, this paper investigates the hydrological responses to climate change and to human activities in the arid Tarim River basin (TRB). The results show that the surface runoff of three headstreams (Aksu River, Yarkant River and Hotan River) of the Tarim River exhibited a significant increasing trend since 1960s and entered an even higher-runoff stage in 1994. In the contrary, the surface runoff of Tarim mainstream displayed a persistent decreasing trend since 1960s. The increasing trend of surface runoff in the headstreams can be attributed to the combined effects of both temperature and precipitation changes during the past five decades. But, the decreasing trend of surface runoff in the mainstream and the observed alterations of the temporal and spatial distribution patterns were mainly due to the adverse impacts of human activities. Specifically, increasingly intensified water consumption for irrigation and the associated massive constructions of water conservancy projects were responsible for the decreasing trend of runoff in the mainstream. And, the decreasing trend has been severely jeopardizing the ecological security in the lower reaches. It is now unequivocally clear that water-use conflicts among different sectors and water-use competitions between upper and lower reaches are approaching to dangerous levels in TRB that is thus crying for implementing an integrated river basin management scheme.